Análise de modelos de séries temporais para a previsão mensal do imposto de renda - Santos, Alan Vasconcelos (2003)
The main objective of this work was to generate predictions, at a monthly frequency, from 1990 to 2001, of income tax revenue. The methodology used was the one of forecast combining. Specifically, exponential smoothing, an ARIMA and VAR with error correction models were pooled to obtain final prediction. Ex-post forecast errors were used to test the performance of the model. Results indicated that combining performs better than individual models, and errors are in an acceptable interval for this type of prediction.